Ditaxis (Euphorbiaceae) from the Brazilian Caatinga, including a new species - Külkamp, Josimar; Iganci, João R. V.; Cordeiro, Inês; Baumgratz, José Fernando A. (Phytotaxa, 2020)
Ditaxis is a Neotropical genus with approximately 50 species, most of them in seasonally dry tropical forests of Brazil, Central America and the Antilles. The Brazilian Caatinga, the largest area of SDTF in South America, harbors three endemic species of Ditaxis, including the new Ditaxis grazielae, hereby described and illustrated. The new species is known from a few localities in the state of Bahia. We provide an identification key for the species occurring in the Caatinga, as well as comments on habitat, distribution and phenology. We also present amended descriptions and typifications for Ditaxis desertorum and D. malpighiacea, and propose D. gardneri as synonym of D. desertorum.